Genetic Diversity of Campylobacter jejuni Isolated From Avian and Human Sources in Egypt - Abd El-Hamid, Marwa I.; Abd El-Aziz, Norhan K.; Samir, Mohamed; El-Naenaeey, El-sayed Y.; Abo Remela, Etab M.; Mosbah, Rasha A.; Bendary, Mahmoud M. (Frontiers in Microbiology, 2019)
Campylobacter jejuni (C. jejuni) are able to colonize and infect domestic poultry and poses risk for humans. The aim of this study was to determine the extent of genotypic diversity among C. jejuni encoding major virulence genes isolated from avian and human sources in Egypt. Furthermore, the short variable region (SVR) of flagellin A (flaA) gene was analysed for the presence of allelic variants. Our results showed that C. jejuni isolates differ in their capacity to harbour each of the virulence genes alone or when present in various combinations. The flaA gene was detected in all C. jejuni strains and none of the strains encoded all the studied virulence genes together. The frequency of cdtC gene was the highest similar among all strains, whereas that of cdtB and iam genes was the most dissimilar When considering C. jejuni strains from the investigated sources, the cdtC gene was the highestmost similar, while the cdtB and iam genes were the most dissimilar. We could identify 13 novel alleles in the analysed strains. The analyses of virulence gene patterns, flaA gene sequences and allelic variants showed that C. jejuni strains from different sources overlapped largely, suggesting potential involvement of poultry in transmitting C. jejuni to humans. We also found that the strains isolated from the same host were highly heterogeneous, with chicken strains exhibiting the highest diversity. Moreover, the human strains were clustered closer to chicken ones than to those from pigeon. The results of this study should be taken into consideration when assessing the epidemiology and risk potential of Egyptian C. jejuni not only in poultry, but also in humans.